FUNGSI KOMISI PENGAWAS PERSAINGAN USAHAMENURUT UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Suka Antara Yasa, I Wayan; Rai Setiabudhi, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2014)
A Business Competition Supervisory Commission is an institution established by the Act No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition ( Act. 5/1999 ) and has the authority to decide disputes in a business competition. However, the Commission is not a judicial institution that is included in Act. No. 48 of 2009 on Judicial Power ( Act. 48/2009 ) . Therefore , the purpose of this study was to determine whether or not recognized the Commission's authority to rule on the dispute of competition in Act. 48/2009 . The method used in this study is a normative research methods . Based on the research, it can be drawn a conclusion that although the Commission is not a judicial institution that is included in Act 48/2009 , but based on the method of argumentum peranalogian, the Commission has the same function as the judiciary , so that the Commission 's decision remains recognized and binding on the parties who violate the provisions of Act. 5/1999.
Keywords: authority, decision, commission, Institute for Justice